2009
DOI: 10.1007/s00464-009-0583-3
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery and cancer: controversies part 1

Abstract: Perhaps there is no more important issue in the care of surgical patients than the appropriate use of minimally invasive surgery (MIS) for patients with cancer. Important advances in surgical technique have an impact on early perioperative morbidity, length of hospital stay, pain management, and quality of life issues, as clearly proved with MIS. However, for oncology patients, historically, the most important clinical questions have been answered in the context of prospective randomized trials. Important cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 175 publications
(169 reference statements)
0
23
0
7
Order By: Relevance
“…EUS visualization can display five distinct layers of the esophageal wall (the echo/ superficial mucosa boundary, the mucosa, the submucosa, the muscularis propria, and the adventitia) and represents an important advance in esophageal cancer staging. The reported sensitivity of EUS in the assessment of T-stage is 85-90%, and the reported accuracy is 70-80% (16,17). EUS also is useful in detecting regional lymphadenopathy and sampling suspicious nodes with fine-needle aspiration (FNA) ( Table 2).…”
Section: Endoscopic Ultrasoundmentioning
confidence: 99%
“…EUS visualization can display five distinct layers of the esophageal wall (the echo/ superficial mucosa boundary, the mucosa, the submucosa, the muscularis propria, and the adventitia) and represents an important advance in esophageal cancer staging. The reported sensitivity of EUS in the assessment of T-stage is 85-90%, and the reported accuracy is 70-80% (16,17). EUS also is useful in detecting regional lymphadenopathy and sampling suspicious nodes with fine-needle aspiration (FNA) ( Table 2).…”
Section: Endoscopic Ultrasoundmentioning
confidence: 99%
“…[28][29][30] However, MIE is very far from being accepted for routine clinical use worldwide due to the steep learning curve and the unproven cost-effectiveness. 31 Moreover, several technical variables (laparoscopy, thoracoscopy, combined steps, prone or supine position, stapled or hand-sewn anastomosis), together with the general poor quality of the published studies, has contributed to the confounded outcomes and oncologic results. 32 Robot-assisted, minimally invasive esophagectomy (RAMIE) facilitates esophageal dissection with enhanced visualization of the three-dimensional fields, allowing the execution of complex maneuvers through the articulated instruments, including lymphadenectomy and visceral anastomoses.…”
Section: Bencini Et Almentioning
confidence: 99%
“…31 Despite the advancements in recent years in laparoscopy (ie, colorectal surgery), the keyhole approach to gastric surgery is still debated and exclusive to a few skilled surgeons, many of them working in Eastern countries. 19,31,50 The limits for the widespread use of laparoscopic gastrectomy (LG) are represented mainly by the technical difficulties in both anastomosis, lymphadectomy and conflicting benefits. Nevertheless, two very comprehensive meta-analyses concluded that LG is better or comparable to open surgery with regards to early and long-term outcomes, although at the price of a longer duration of surgery.…”
mentioning
confidence: 99%
“…Einer tendenziell längeren Operationsdauer bei laparoskopischer Chirurgie stehen eine kleinere Inzisionslänge mit geringerer postoperativer Schmerzintensität, weniger Wundinfekten, kürzerer Krankenhausverweildauer, niedrigerem intraoperativen Blutverlust, einem besseren kosmetischen Ergebnis und weniger Narbenhernien sowie eine höhere Patientenzufriedenheit gegenüber [7]. …”
Section: Introductionunclassified